Prácticas Culturales para la Producción Comercial de Fresas en Florida - Bielinski M. Santos; Henner A. Obregón (EDIS)
HS1160, a 15-page illustrated Spanish language fact sheet by Bielinski M. Santos and Henner A. Obregón, describes strawberry production in Florida, its history, cultivar development, and cultural practices. Published by the UF Department of Horticultural Sciences, October 2009.